Exploring the Influence of Digital Transformation, Change Management, and Employee Engagement on Organizational Performance of Non Profit Organization in Indonesia - Komariyah, Imas; Ismawanti, Resty (IJBLE Scientific Publications Community Inc., 2024)
This study explores the influence of digital transformation, change management, and employee engagement on the organizational performance of nonprofit organizations in Indonesia. Using a quantitative approach with 250 respondents from various nonprofit sectors, the results indicate that all three factors significantly impact organizational performance. Change management emerges as the most influential variable and mediates the effects of digital transformation and employee engagement. These findings highlight the critical role of effective change management in ensuring that digital initiatives and employee engagement efforts translate into improved organizational outcomes. The study emphasizes the importance of strategic investments in technology, fostering employee engagement, and strong change management practices to enhance nonprofit performance. Recommendations for further research are also provided to expand the understanding of these relationships in different contexts.